Sistem Multi Partai Indonesia Dan Sistem Perwakilan Politik Kelurahan Dompak Tanjung Pinang - Jauzari Helmi; Reski Apriyani; Syahriful Ahyar; Raja Nur Hafriza (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
The aim of this research is to understand the multi-party system in Indonesia, the political representation system in Indonesia, and the relationship between these systems with the political dynamics in Kelurahan Dompak, Tanjung Pinang. A descriptive qualitative research method was employed, utilizing interviews, observations, and document analysis to gain an in-depth understanding of the phenomenon. The results indicate that Indonesia's political system provides opportunities for various political parties to participate in the political process and elections. At the local level, the relationship between political parties, the community, and the government is crucial in the context of democracy. Although the dynamics of political money influence the public's perception of assistance provided by candidates, the principles of political equality and freedom remain the foundation of the political representation system aimed at forming a government that is responsive to the needs of the people.